FORMATION OF «FALSE ANNUAL RINGS» ON SCALES OF JUVENILE COHO SALMON ONCORHYNCHUS KISUTCH IN LAKE KURAZHECHNOYE (KAMAKOVSKAYA LOWLAND — KAMCHATKA RIVER BASIN) - V. F. Bugaev; G. V. Bazarkin; D. P. Pogorelova (Известия ТИНРО, 2019)
During spring-summer flood (in mid May — July), transit underyearlings of coho salmon, having or having no scales, migrate to Lake Kurazhechnoye at the lower Kamchatka River, where resident coho salmon never spawn. In this case, additional zones of closely–spaced sclerites (ZCS) can be formed on their scales because of feeding change (additional ZCS of the 1st type). Seasonal growth restarts and annual zone of close sclerites (annual ring) forms in May (or in early June for a part of juveniles) on scales of yearlings and elder coho salmon wintered in Lake Kurazhechnoye. In late July — August or sometimes later, other additional ZCS could form on the scale of juvenile coho salmon (ages 1+ and 2+) in the lake (additional ZCS of the 2nd type) because of their switching to feeding by fish (ninespine stickleback Pungitius pungitius, threespine stickleback Gasterosteus aculeateus, and smelt Hipomesus olidus). Rate of the sclerites forming was examined for the coho juveniles of age 1+ in Lake Kurazhechnoye in 2001 and evaluated as 8.52 days/sclerite, on average (one sclerite was formed in 9.18 days between June 13 — July 5 but in 7.86 days between July 5–23).